UPAYA PAKSA (DWANG MIDDELEN) DALAM DUGAAN TERJADINYA TINDAK PIDANA BAGI PENYIDIK - Bagus Teguh Santoso (Universitas Islam Darul Ulum, 2022)
The supreme court didn’t make the gradation on the evidence law in the process of the law enforcement on the first stage/pre-trial (investigation and introgation) and the second stage/trial (prosecution and verdict). Meanwhile, the provisions of article 184 KUHAP is related with the provisions of the next article 185, 186, 187, 188, and 189 KUHAP. That proves that the gradation of legal evidence in article 184 is for the second stage/ trial process. The research method used in this research is normative legal research. The research approach used is the statutory approach, the conceptual approach and the cases approach to coercive measures (dwang middelen) in the alleged occurrence of criminal acts for investigators based on the Criminal Procedure Code and the Constitutional Court Decision Number: 21/ PUU-XII/2014. This study aims to analyze disharmony as a legal consequence of the Constitutional Court Decision No. 21/PUU-XII/2014. If the verdict of supreme court aquo has the character final and binding, then after 30 days it was decided and declared in the gazette. As the law effect, all measures from the investigator were guided by KUHAP, in the frame of the force effort (dwang middelen) when the determination of the suspect, the arrest, and the detention is called as the breach of the legality principle and the rechtmatigeheid van bestur principle. That measures is null and void (neitigheid van rechtswege), therefore when tested by the pre-trial process about that measures, then the lawsuit filed by the applicant is very feasible and rasionable based on the law and appropriate to be accepted by the judge of pre-trial examiner.